Increased cord-blood eosinophil counts and prenatal exposure to tobacco smoke: A concern for development of atopy early in childhood - (:unkn) unknown (My University, 2002)
Objective: In adults several reports indicate that eosinophil counts and serum IgE levels increase in tandem with the number of cigarettes smoked. Several conflicting results have also been reported regarding prenatal cigarette smoke exposure and its effects on fetal immunoglobulin levels. Thus we surveyed cord-blood cotinine, IgE concentrations and eosinophil counts in 142 neonates in relation to parental smoking during pregnancy. Methods: This study was performed at Marmara University Hospital between July 1995 and May 1996. Pregnant women were selected at random. Cord-blood was collected at delivery and maternal urine samples were collected within the first hour after delivery. Complete blood count and differential counts were measured in the cord-blood samples within the first hour after delivery. Serum was separated from the cord-blood within 2 hours of collection and the specimens were stored at -30°C until assay, for cotinine and IgE. Results: Maternal urinary cotinine/creatinine ratio (UCCR) was used as a biologic marker of passive smoke exposure. Maternal UCCR and cord-blood cotinine levels were significantly correlated, and both were highest in the active smokers and their infants. Cord-blood eosinophil counts rose in tandem with maternal UCCR. Cord-blood IgE levels were correlated with maternal UCCR only for nonatopic mothers. No relationship was found between cord-blood cotinine, IgE levels, and eosinophil counts. Conclusion: We conclude that, maternal smoking, whether active and/or passive, affects cord-blood eosinophil counts in women without atopy. The implication of these findings in the development of atopy later in life have yet to be identified.
Keywords: Atopy; Cord-blood; Cotinine; Eosinophil; IgE; Newborn; Smoking